Book Review. Issue 2 (1st October 2018) - Petrie, Kevin
Art and Design Pedagogy in Higher Education – Knowledge, Values and Ambiguity in the Creative Curriculum, Susan Orr and Alison Shreeve (2018) Oxford: Routledge, 168 pages, ISBN 978-1-13821-941-0, h/bk, £105